2016
DOI: 10.1007/978-3-319-44805-3_6
|View full text |Cite
|
Sign up to set email alerts
|

Skeuomorphic Reassurance: Personhood and Dementia

Abstract: This paper introduces the concept of 'skeomorphic reassurance' as a guiding principle for human interfaces in technological development and design, particularly for older people and people with dementia (PwD). Skeuomorphs exhibit decorative design elements reminiscent of 'parent' objects that incorporated such design elements because they were structurally integral. Human interfaces adopted by new technologies need to be carefully balanced between novelty and recognisability.The philosophy of personhood is dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Fitzpatrick et al (2015, p 18) also recommend that in this area "rigorous ethical reflection" is required to complement the application of VSD. Our present reflection on ethical notions of power is an attempt, in part, to address this need, as was the recent work of Kreps et al (2016), which explored the design of technology artefacts (not using VSD) for people with age-related cognitive declines, through the interpretive lens of notions of personhood, recommending the incorporation of skeuomorphs a form of design latencyin technological development.…”
Section: Vsd and The Domain Of Age-related Cognitive Declinesmentioning
confidence: 99%
“…Fitzpatrick et al (2015, p 18) also recommend that in this area "rigorous ethical reflection" is required to complement the application of VSD. Our present reflection on ethical notions of power is an attempt, in part, to address this need, as was the recent work of Kreps et al (2016), which explored the design of technology artefacts (not using VSD) for people with age-related cognitive declines, through the interpretive lens of notions of personhood, recommending the incorporation of skeuomorphs a form of design latencyin technological development.…”
Section: Vsd and The Domain Of Age-related Cognitive Declinesmentioning
confidence: 99%
“…Skeuomorphic icons (SIs) rely on features such as textures, shadows, and highlights to mimic real-world objects. Some scholars believe that SIs require less mental effort to process and are more suitable for older adults with cognitive impairments [17], while flat icons (FIs) eschew real-world elements by removing the three-dimensional (3D) design elements, unifying graphic design, and using simpler colors [16,18,19]. FIs are more popular among young people [18,20].…”
Section: Introductionmentioning
confidence: 99%
“…Interactive interfaces for older people should be simple and easy to navigate, with all functions and navigation visible and directly focused on the page, allowing for better and faster navigation and retrieval by older people (Balata et al, 2015 ). Using icons and animations that contain more pictorial information to represent objects, materials, or people in everyday life can help older people to better identify and access information, and such icons are better adapted to older people, the higher older people rate the stylistic design of such icons (Cho et al, 2015 ; Blaynee et al, 2016 ; Kreps et al, 2016 ; Zhou et al, 2017 ). Using objective eye-movement data, it was found that retrieval using flat icons tends to distract users, take longer to perform the task and increase their cognitive load compared to anthropomorphic icons (Burmistrov et al, 2015 ; Spiliotopoulos et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%